2018
DOI: 10.1111/trf.14964
|View full text |Cite
|
Sign up to set email alerts
|

An early increase of CD56bright natural killer subset as dominant effect and predictor of response to extracorporeal photopheresis for graft‐versus‐host disease

Abstract: BACKGROUND: CD56 bright natural killer (NK) regulatory cells were recently shown to display a differential impact on the risk of developing extensive chronic graft-versus-host disease (GVHD). To date no study has definitively established which immune populations are most responsible for the immunomodulatory effects or response to extracorporeal photopheresis (ECP) for GVHD. STUDY DESIGN AND METHODS:To test the role of CD56 bright NK cells in ECP, a prospective enhanced flow cytometry follow-up of immune subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
4
21
2
1
Order By: Relevance
“…Although extracorporeal photopheresis treatment is widely used as a second-line treatment of GvHD, the exact “pharmaceutical” mechanism of this therapy remains unclear. There are no hard facts or data points that can be used to predict the clinical efficacy of an ECP apheresis product [18, 19], although there is some indication that distinct cell populations within the recipient might be a prerequisite for successful treatment [20]. A factor that can be measured as quality control of ECP therapy is the dose of apoptotic MNCs [21] or the number of lymphocytes and MNCs/kg body weight given per single procedure [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although extracorporeal photopheresis treatment is widely used as a second-line treatment of GvHD, the exact “pharmaceutical” mechanism of this therapy remains unclear. There are no hard facts or data points that can be used to predict the clinical efficacy of an ECP apheresis product [18, 19], although there is some indication that distinct cell populations within the recipient might be a prerequisite for successful treatment [20]. A factor that can be measured as quality control of ECP therapy is the dose of apoptotic MNCs [21] or the number of lymphocytes and MNCs/kg body weight given per single procedure [22].…”
Section: Discussionmentioning
confidence: 99%
“…This led us to speculate that low‐dose IL‐2 may target similar pathways to HPIV3 to contract T eff cells. Several reports have revealed that high IL‐2 availability may induce NK cells to kill autologous T cells .…”
Section: Discussionmentioning
confidence: 99%
“…This was highly correlated with a profound treatment response resulting in a reduction in brain inflammatory activity and a marked reduction in the number of magnetic resonance imaging (MRI) gadolinium (Gd)‐enhancing lesions . Moreover, low levels of CD56 bright NK cells have been associated with chronic GVHD, and an early increase of CD56 bright NK cells is considered a predictor of response to extracorporeal photopheresis (ECP) treatment for GVHD . In addition, a recent study demonstrated that IL‐2 treatment combined with ECP led to enhanced CD56 bright NK cells compared with ECP alone .…”
Section: Introductionmentioning
confidence: 99%
“…Further, in an in vivo model of ECP-modulation of rheumatoid arthritis, only ECP-treated splenocytes from arthritogenic donors could suppress inflammation, whereas those from healthy donors had no significant effect (120). Such and that their longitudinal dynamics may correlate with the grade of response (58) observations suggest that supply of apoptotic cells alone is insufficient to control ongoing severe inflammatory diseases. It is of note that most of the studies using apoptotic cell therapy to prevent allograft rejection use donor cells that are from healthy donors and are thus from an immune environment that is in the steady state and the cells are resting or non-activated.…”
Section: Immunological Mechanisms Of Ecp Actionmentioning
confidence: 98%
“…The distinction between genuine ECP responses from milder forms of GVHD that may resolve spontaneously will need randomized clinical trials. On the other hand, these data may indicate that a minimum dose of, and hematopoietic capability, to supply ECPtreated T-cells is needed to exert therapeutic effect or that the infusion includes circulating allo-reactive T-cell clones (52,113) More recently, Iniesta et al (58) reported in 2018 a prospective analysis of 32 GvHD patients undergoing 552 ECP treatments for both, investigating correlation between response to ECP and CD56 bright natural killer (NK) cell population. 11 aGvHD and 21 cGvHD patients underwent ECP treatment during a minimum 3-month period, using a standard ECP protocol, with 1-2 procedures every week for 6 weeks, followed by one procedure every 2 weeks for 6 weeks, then one procedure every month until greatest response was seen.…”
Section: Immunological Mechanisms Of Ecp Actionmentioning
confidence: 99%